Akhlak Tasawuf And Ethical Competence Of The Future English Teachers - Amanda Agni Oktavia Ramadhani; Siti Rahmawati; Roshim Ahmad Musyaffa; Shella Aulia Putri; Raysha Ramadhani; Najwa Amalia (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
Sufism (tasawuf) approaches in education make a significant contribution to addressing ethical competence in the classroom, particularly for future English teachers. This article examines how Sufism principles can strengthen morality and ethics in the learning process. Sufism, with its emphasis on cleansing the heart and spiritual upliftment, offers a holistic method to educate students not only intellectually but also morally and emotionally. Through the Sufism approach, teachers can create a learning environment imbued with spiritual values such as honesty, patience, compassion, and respect. This research employs a qualitative method with a literature study analysis to explore how Sufi concepts can be applied to teaching strategies. The findings show that integrating Sufism into education can foster higher moral awareness among students and help teachers create a harmonious and productive classroom atmosphere. By applying this approach, future English teachers can become role models in teaching moral values